JEJARING SOSIAL: TRANSFORMASI KOMUNIKASI DALAM ERA DIGITAL - Alfiansyah, Ithomas; Anshori, Isa (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2024)
Social networks have grown rapidly in the digital age and can significantly change the way we communicate and interact. This transformation has affected the way humans interact, share information, and form social relationships. This research examines the changes in social network communication in the digital era. This research seeks relevant sources such as books, scientific journals, and articles related to social networking and communication changes in the digital era. The results of this study provide an overview of changes in communication patterns, language use, digital identity, and the social and cultural effects that accompany changes in communication in social networks. Through an in-depth understanding of the phenomenon, the research shows that social networks have changed the traditional communication paradigm, enabling the creation of new spaces for the direct exchange of information, opinions, and experiences. Social networks also influence the way we construct and perform online identities, shaping the unique dynamics of social interaction. The implications of this research can provide individuals, societies, communities, and organizations with insights into changes in social network communication and highlight the importance of further research in this area.